Clonal propagation of Tetragonolobus palaestinus Bioss: A Jordanian medical plant - Mawadda MHERAT; Mohammad SHATNAWI; Rida SHIBLI; Tamara QUDAH; Saida ABU MALLOH; Tamadour AL-QUDAH (Acta Agriculturae Slovenica)
Tetragonolobus palaestinus Bioss (Aljalaton) is one of the Jordanian medicinal plants that can be used to treat stomach pain and some infections. This study was done in order to establish optimal in vitro propagation method for T. palaestinus. Factors of in vitro shooting, rooting, and acclimatization of the in vitro Tetragonolobus palaestinus seedlings were studied using different growth regulators. For in vitro shooting, different cytokinins including benzylamino purine (BAP), kinetin, TDZ, and zeatin were used in increasing concentrations (0.0, 0.3, 0.6, 0.9, 1.2, 1.5, and 2.0 mg l-1). Using benzylamino purine (BAP produced a maximum of 2.0 shoots/explants on Murashige and Skoog (MS) medium supplemented with 0.3 mg l-1. Moreover, the effect of different concentrations of IBA (indole-3-butyric acid), IAA (indole-3-acetic acid), andnaphthalene acetic acid (NAA) was evaluated for in vitro rooting. The highest number of roots (4.06 roots/explant) was obtained on MS medium supplemented with 0.3 mg l-1 IBA. All of the plants (100 %) were grown normally after the acclimatization process. Based on these results simple protocol of T. palaestinus in vitro culture was optimized for the first time which can be utilized to do more studies on cell culture and production of active secondary metabolites.